COGNITIVE DEPTH OF TEACHING AND LEARNING PROCESS IN BIOLOGY FROM 7TH TILL 9TH GRADE - Bērtule, Dace; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
From OECD PISA Science test results presented in 2016 shows that in Latvia only 3,4% of students performance is in accordance to the 5th and 6th performance level (higher order cognitive skills (HOCS) measured), which is below OECD average. In Latvia from 2016 started Curriculum Development and Implementation project, which one of the priorities is student’s ability to apply HOCS (higher order cognitive skills) to improve these results. The development of deeper thinking (cognitive activity) is one of the most advanced skills in all subjects, including biology. In order to reduce the risks, it is necessary to analyze introducing new reforms the opportunities for students to develop HOCS through biology lessons and textbooks in current teaching and learning process. In previous researches it was found out that all items with context of 9th grade biology in the Latvia’s National level Science test (period 2015-2017) were measuring only low and average depth and no one was in high cognitive level as opposed to the PISA framework. It is required to study reasons of that more deeply. The research goal is to analyze cognitive depth of given tasks that students have the opportunity to do in the lessons of biology, biology textbooks from 7th till 9th grade and with 9th grade biology tasks in Latvia’s National level Science tests from years 2015 till 2017 and to compare these three cognitive depth results to the PISA 2015 Science framework. To find out cognitive depth of given tasks, there were analysed 31 samples of biology lessons and 6 biology textbooks for grades 7th till 9th.